PERFORMANCE EVALUATION ANALYSIS OF SOUTH NIAS DISTRICT GOVERNMENT - Purba, Sahala; Laia, Merisa Aguspani; Barus, Ike Anggreani; Samosir, Yosafat Renovaldo; Sinaga, Lusia Shelomita (Kajian Akuntansi, 2024)
This research aims to determine the financial performance of Regional Government from various aspects. This research is a quantitative descriptive study with the subject of the South Nias Regency Regional Government Financial Report for the 2013-2022 period. The research results of the regional financial independence index have an average value of 2.06%, which is still very low. The average regional financial dependency is 85.96%, which is still high. The average decentralization ratio is 12.06% in the low category. The average level of effectiveness of PAD is 68.02%, which is quite high. The average PAD efficiency level is 46% which is quite high. The average regional tax efficiency level is 1% in the ineffective category. The average regional tax efficiency level is 2% in the very good/efficient category. The BUMD contribution level ratio shows an average value of 1%, and the contribution received by BUMD is still low.   Keywords     : Financial Performance, Financial Report Analysis, and South Nias Regency Government